Shotgun slug wads as a marker of range of fire: A case report and novel firearm testing data. Issue 6 (26th July 2021) - Multan, Michael; Moore, Shannon; Forest‐Allard, Éloïse; Orde, Matthew M.
Abstract: Assessment of wound characteristics and the identification of various constituents of firearm discharge at autopsy play a key role in the determination of range of fire. In relation to wounds caused by shotguns, identification of the wad within the wound track, or of injury caused by the wad, is typically thought to suggest a fairly close range of fire. We present a case of a fatality due to a shotgun slug wound where the presence of the wad within the decedent's body was proposed by defense at criminal trial to favor accidental close range discharge during a struggle for the weapon—as opposed to the prosecution's contention of intentional firing of the weapon from a greater range and through an intermediate target. We undertook test firing of a shotgun of similar design to that which was fired during the interaction (a 12‐gauge pump‐action shotgun) using shotshells consistent with the slug that was recovered from the body (Winchester Super X brand), which demonstrated that the non‐attached fiber wad present in this shotshell design can accompany the slug over distances of at least up to 22 feet (6.7 m) and even after transit through intermediate targets such as a vehicle headrest. These novel data provide assistance with estimation of range of fire in instances of injuries caused by shotgun slugs.